Penggunaan Buku Ajar Pembelajaran IPA I Untuk Melatih Kecakapan Mengajar Mahasiswa - Fitria Eka Wulandari; Noly Shofiyah (Universitas Muhammadiyah Sidoarjo, 2018)
At this time, there is no textbook for the Science Learning I courses at th Science Education Study Program and the way to teach students is still based on the power point used by the lecturer. As consequences, the student learning process was to be less than optimal in getting learning references. The purpose of this study was to describe the teaching skills of students after the implementation of the Science Learning Textbook I. This study used one shot case study design. The results showed that the use of Science Learning Textbook I could train students' teaching skills. The average student teaching skills were 3.45 with a percentage of 78 categorized Good.